Flame-retardant adhesive for plywood and preparation method thereof

By combining modified hydrotalcite of organic/inorganic composite flame retardant with organophosphorus flame retardant, the problem of poor dispersion of existing flame retardants in adhesives is solved, the flame retardant and mechanical properties of plywood are improved, a stable carbon layer is formed to block heat and oxygen, and dilute combustible gases.

CN120699569APending Publication Date: 2025-09-26JIANGMEN ZICHUANG INTELLIGENT TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510896217.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing flame retardants have poor dispersion in adhesives, resulting in poor flame retardant performance and affecting the mechanical properties of the adhesive. Traditional halogen-based flame retardants have the problem of corrosive smoke. The amount of inorganic flame retardants added is large and the polarity difference with the adhesive base material is large, which affects the effect.

Method used

An organic/inorganic composite flame retardant containing P, N, Si, Mg, and Al elements is used to form a stable organic/inorganic composite flame retardant system by combining modified hydrotalcite with an organophosphorus flame retardant, thereby improving dispersibility and enhancing flame retardant effects.

Benefits of technology

The flame retardant is evenly dispersed in the adhesive, which improves the flame retardancy and mechanical properties of the plywood, avoids the defects of traditional flame retardants, forms a stable carbon layer to block heat and oxygen, and dilutes combustible gases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120699569A_ABST
    Figure CN120699569A_ABST
Patent Text Reader

Abstract

The invention relates to a flame-retardant adhesive for plywood and a preparation method of the flame-retardant adhesive, and belongs to the technical field of wood adhesives. The flame-retardant adhesive for the plywood is prepared from the following components in parts by weight: 52 to 70 parts of EVA (Ethylene-Vinyl Acetate) emulsion, 28 to 33 parts of methyl acrylate, 15 to 21 parts of acrylamide, 10 to 13 parts of N-hydroxy acrylamide, 12 to 16 parts of modified hydrotalcite, 3 to 5 parts of an organic phosphorus flame retardant, 0.8 to 1.0 part of an initiator and 0.8 to 1.5 parts of an auxiliary agent. The organic / inorganic composite flame retardant containing P, N, Si, Mg and Al flame-retardant elements overcomes the defect of single performance of flame retardants, and is good in flame-retardant effect and good in stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wood adhesives and relates to a flame retardant adhesive for plywood and a preparation method thereof. Background Art

[0002] Wood, with its environmentally friendly, biodegradable, and renewable properties, as well as its high specific strength, excellent electrical insulation, and rich natural porous structure, plays a vital role in packaging, home improvement, construction, and other fields. However, global resources of high-quality natural wood are becoming increasingly scarce. To increase the utilization of wood materials, adhesives are combined with lower-quality wood materials such as shavings, wood chips, branches, and small-diameter lumber to create high-performance artificial boards.

[0003] At present, traditional flame retardants have many disadvantages. Although halogen-based flame retardants have high flame retardant effects, high cost-effectiveness, and wide applicability, the hydrogen halide gas released by their decomposition during combustion is highly corrosive and produces a large amount of smoke. In recent years, their use has been gradually restricted. Inorganic flame retardants such as aluminum hydroxide and magnesium hydroxide are widely available, low in price, and release less smoke and toxic gases when burned. However, when used alone, the amount added is large, and the polarity is quite different from that of the adhesive base material, making it difficult to disperse evenly. This results in the inability to formulate highly effective flame-retardant adhesives and also affects the mechanical properties of the adhesive. In halogen-free flame retardant systems, nitrogen-based and phosphorus-based flame retardants have low flame retardant efficiency, among which phosphorus-based flame retardants are expensive and limited in variety. Additive flame retardants not only require large addition amounts, but also reduce the mechanical properties of the matrix material, such as tensile strength and flexibility, affecting the effectiveness of the adhesive in practical applications.

[0004] Hydrotalcite, an inorganic material with a unique layered structure, has recently demonstrated great potential in the flame retardant field. It is non-toxic, non-volatile, highly stable, and designable. The metal oxides produced by thermal decomposition form a stable carbon layer on the material's surface, acting as a heat and oxygen barrier. The water molecules produced by decomposition dilute the concentration of combustible gases and reduce the ambient temperature. However, pure hydrotalcite has poor dispersibility in organic adhesive systems, limiting its full flame retardant properties. Summary of the Invention

[0005] The purpose of the present invention is to provide a flame-retardant adhesive for plywood and a preparation method thereof. The flame-retardant adhesive for plywood prepared by the present invention contains an organic / inorganic composite flame retardant containing flame-retardant elements of P, N, Si, Mg, and Al, which overcomes the disadvantage of single performance of flame retardants. The organic / inorganic composite flame retardant has good flame retardant effect and good stability.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A flame-retardant adhesive for plywood comprises the following components in parts by weight: 52-70 parts of EVA emulsion, 28-33 parts of methyl acrylate, 15-21 parts of acrylamide, 10-13 parts of N-hydroxyacrylamide, 12-16 parts of modified hydrotalcite, 3-5 parts of organophosphorus flame retardant, 0.8-1.0 part of initiator and 0.8-1.5 parts of auxiliary agent.

[0008] As a preferred technical solution of the present invention, the organophosphorus flame retardant is one or more of phenylphosphinic acid, dimethyl methylphosphonate, diethyl ethylphosphonate, and diphenyl phenylphosphonate. Preferably, the organophosphorus flame retardant is composed of phenylphosphinic acid and dimethyl methylphosphonate in a mass ratio of 3:1.

[0009] As a preferred technical solution of the present invention, the initiator is a water-soluble peroxide initiator, and the water-soluble peroxide initiator is one or both of ammonium persulfate and potassium persulfate.

[0010] As a preferred technical solution of the present invention, the auxiliary agent is composed of polyethylene glycol 400 and sodium lauryl sulfate in a mass ratio of 1:1.

[0011] As a preferred technical solution of the present invention, EVA emulsion, EVA is also known as ethylene-vinyl acetate copolymer, model 250, VA content is 28%, DuPont Company, USA.

[0012] As a preferred technical solution of the present invention, the preparation method of the modified hydrotalcite comprises the following steps:

[0013] S1. Dry the hydrotalcite in an oven at high temperature, cool it, add anhydrous ethanol and a modified silane coupling agent, mix them ultrasonically, adjust the pH value, heat and stir, filter and take the solid, wash it, and vacuum dry it to obtain a prefabricated hydrotalcite;

[0014] S2. Stir and disperse the prefabricated hydrotalcite and pure ethanol, slowly add furfural and stir at a constant temperature, remove the liquid by centrifugation, rinse the solid, and dry it in a vacuum oven to obtain the product.

[0015] As a preferred technical solution of the present invention, in step S1, the high-temperature drying is vacuum drying at 100-120°C for 4-6 hours to remove physically adsorbed water, the particle size of the hydrotalcite is 50-100 nm, the cooling is cooling to room temperature, the ultrasonic mixing is ultrasonic mixing at 200-300W power for 5-8 minutes, the pH value is adjusted to 7.5, the heating and stirring is stirring at 40-52°C for 5-6 hours, the cleaning is washing three times with anhydrous ethanol, the vacuum drying is vacuum drying at 80°C for 10-12 hours, and the mass ratio of the hydrotalcite, anhydrous ethanol and modified silane coupling agent is 20-23:80-100:12-16.

[0016] As a preferred technical solution of the present invention, in step S2, the stirring and dispersing is stirring at a speed of 300-500 rpm for 15-30 minutes, the constant temperature stirring is stirring at a constant temperature of 58-65°C for 4-5 hours, the rinsing is rinsing four times with pure ethanol, and the vacuum drying is vacuum drying at 90°C to constant weight. The mass ratio of the prefabricated hydrotalcite, pure ethanol and furfural is 18-20:60-80:2.2-2.6.

[0017] As a preferred technical solution of the present invention, the preparation of the modified silane coupling agent comprises the following steps:

[0018] L-cysteine ​​is added to a photoinitiator and a solvent and ultrasonically dispersed, an inert gas is introduced to form an inert gas atmosphere, the mixture is placed under ultraviolet light, a silane monomer is slowly added with magnetic stirring, the solvent is removed by rotary evaporation, and vacuum drying is performed to obtain the product.

[0019] As a preferred technical solution of the present invention, in the preparation of the modified silane coupling agent, the ultrasonic dispersion is ultrasonic at a power of 150-200W for 10-15 minutes, the inert gas is nitrogen gas, the ultraviolet lamp irradiation is ultraviolet irradiation at a wavelength of 365nm, the magnetic stirring is stirring at a speed of 300-500rpm for 3-4 hours, the mass ratio of L-cysteine, silane monomer, photoinitiator and solvent is 24-26:28-32:0.10-0.12:200-220, the photoinitiator is photoinitiator 1173, and the silane monomer is silane coupling agent NQ62, i.e., diethylenetriaminopropyltrimethoxysilane.

[0020] The present invention discloses a method for preparing the flame retardant adhesive for plywood, comprising the following steps:

[0021] Preheat the EVA emulsion to 60-65°C, add methyl acrylate, acrylamide and N-hydroxyacrylamide, modified hydrotalcite, organophosphorus flame retardant and additives, stir, cool, add initiator and continue stirring to obtain the product.

[0022] Beneficial effects of the present invention:

[0023] The flame retardant adhesive for plywood prepared by the present invention contains an organic / inorganic composite flame retardant of flame retardant elements P, N, Si, Mg and Al, which overcomes the disadvantage of single performance of flame retardants. The organic / inorganic composite flame retardant has good flame retardant effect and good stability.

[0024] Other features and advantages of the present invention will be described in the following description and will become apparent from the description or learned through practice of the present invention. The objectives and other advantages of the present invention can be achieved and obtained by means of the structures specifically indicated in the description, claims, and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the FTIR spectrum of the modified silane coupling agent;

[0026] Figure 2 is the FTIR spectrum of modified hydrotalcite. DETAILED DESCRIPTION

[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0028] Example 1

[0029] A flame-retardant adhesive for plywood comprises the following components in parts by weight: 52 parts of EVA emulsion, 28 parts of methyl acrylate, 15 parts of acrylamide, 10 parts of N-hydroxyacrylamide, 12 parts of modified hydrotalcite, 3 parts of an organophosphorus flame retardant, 0.8 parts of an initiator, and 0.8 parts of an auxiliary agent, wherein the organophosphorus flame retardant is composed of phenylphosphinic acid and dimethyl methylphosphonate in a mass ratio of 3:1, the initiator is ammonium persulfate, and the auxiliary agent is composed of polyethylene glycol 400 and sodium dodecylsulfonate in a mass ratio of 1:1.

[0030] The preparation method of the modified hydrotalcite comprises the following steps:

[0031] S1. Place 50 nm hydrotalcite in an oven, vacuum dry at 100 ° C for 4 h to remove physically adsorbed water, cool to room temperature, add anhydrous ethanol and a modified silane coupling agent, ultrasonicate at 200 W power for 5 min, adjust the pH value to 7.5, heat to 40 ° C and stir for 5 h, filter and collect the solid, wash it three times with anhydrous ethanol, and vacuum dry it at 80 ° C for 10 h to obtain a prefabricated hydrotalcite, wherein the mass ratio of the hydrotalcite, anhydrous ethanol and modified silane coupling agent is 20:80:12;

[0032] S2. The prefabricated hydrotalcite and pure ethanol were stirred at 300 rpm for 15 minutes, furfural was slowly added and stirred at a constant temperature of 58°C for 4 hours, the liquid was removed by centrifugation, the solid was rinsed four times with pure ethanol, placed in an oven, and vacuum-dried at 90°C to constant weight to obtain a modified hydrotalcite, wherein the mass ratio of the prefabricated hydrotalcite, pure ethanol, and furfural was 18:60:2.2.

[0033] Wherein, the preparation of the modified silane coupling agent comprises the following steps:

[0034] L-cysteine ​​was added to a photoinitiator and a 95% volume fraction ethanol solution, and the mixture was ultrasonically treated at a power of 150 W for 10 minutes. Nitrogen gas was introduced to form an inert gas atmosphere, and the mixture was placed under ultraviolet light of 365 nm wavelength. A silane monomer was slowly added and magnetic stirring was performed at a speed of 300 rpm for 3 hours. The solvent was rotary evaporated and the mixture was vacuum dried at 80° C. to constant weight to prepare a modified silane coupling agent. The mass ratio of the L-cysteine, silane monomer, photoinitiator and ethanol solution was 24:28:0.10:200. The photoinitiator was photoinitiator 1173, and the silane monomer was silane coupling agent NQ62.

[0035] A method for preparing a flame retardant adhesive comprises the following steps:

[0036] Preheat the EVA emulsion to 60°C, add methyl acrylate, acrylamide and N-hydroxyacrylamide, modified hydrotalcite, organophosphorus flame retardant and additives and stir, cool, add initiator and continue stirring to obtain a flame retardant adhesive.

[0037] Example 2

[0038] A flame-retardant adhesive for plywood comprises the following components in parts by weight: 58 parts of EVA emulsion, 30 parts of methyl acrylate, 17 parts of acrylamide, 11 parts of N-hydroxyacrylamide, 13 parts of modified hydrotalcite, 3.7 parts of an organophosphorus flame retardant, 0.87 parts of an initiator, and 1 part of an auxiliary agent, wherein the organophosphorus flame retardant is composed of phenylphosphinic acid and dimethyl methylphosphonate in a mass ratio of 3:1, the initiator is ammonium persulfate, and the auxiliary agent is composed of polyethylene glycol 400 and sodium dodecylsulfonate in a mass ratio of 1:1.

[0039] The preparation method of the modified hydrotalcite comprises the following steps:

[0040] S1. Place a 70 nm particle size hydrotalcite in an oven, vacuum dry it at 105°C for 4.5 hours to remove physically adsorbed water, cool it to room temperature, add anhydrous ethanol and a modified silane coupling agent, ultrasonicate it at 235 W power for 6 minutes, adjust the pH value to 7.5, heat it to 44°C and stir it for 5.5 hours, filter the solid, wash it three times with anhydrous ethanol, and vacuum dry it at 80°C for 10.5 hours to obtain a prefabricated hydrotalcite, wherein the mass ratio of the hydrotalcite, anhydrous ethanol and modified silane coupling agent is 21:87:13;

[0041] S2. The prefabricated hydrotalcite and pure ethanol were stirred at 365 rpm for 20 min, furfural was slowly added and stirred at a constant temperature of 60°C for 4.3 h, the liquid was removed by centrifugation, the solid was rinsed four times with pure ethanol, placed in an oven, and vacuum-dried at 90°C to constant weight to obtain a modified hydrotalcite, wherein the mass ratio of the prefabricated hydrotalcite, pure ethanol, and furfural was 19:68:2.3.

[0042] Wherein, the preparation of the modified silane coupling agent comprises the following steps:

[0043] L-cysteine ​​was added to a photoinitiator and a 95% volume fraction ethanol solution, and the mixture was ultrasonically treated at a power of 165 W for 12 minutes. Nitrogen gas was introduced to form an inert gas atmosphere, and the mixture was placed under ultraviolet light of 365 nm wavelength. A silane monomer was slowly added and magnetic stirring was performed at a speed of 365 rpm for 3.5 hours. The solvent was removed by rotary evaporation, and the mixture was vacuum dried at 80° C. to constant weight to prepare a modified silane coupling agent. The mass ratio of the L-cysteine, silane monomer, photoinitiator and ethanol solution was 24.5:29:0.11:205. The photoinitiator was photoinitiator 1173, and the silane monomer was silane coupling agent NQ62.

[0044] A method for preparing a flame retardant adhesive comprises the following steps:

[0045] Preheat the EVA emulsion to 62°C, add methyl acrylate, acrylamide and N-hydroxyacrylamide, modified hydrotalcite, organophosphorus flame retardant and additives and stir, cool, add initiator and continue stirring to obtain a flame retardant adhesive.

[0046] Example 3

[0047] A flame-retardant adhesive for plywood comprises the following components in parts by weight: 64 parts of EVA emulsion, 31 parts of methyl acrylate, 19 parts of acrylamide, 12 parts of N-hydroxyacrylamide, 15 parts of modified hydrotalcite, 4.5 parts of an organophosphorus flame retardant, 0.95 parts of an initiator, and 1.3 parts of an auxiliary agent, wherein the organophosphorus flame retardant is composed of phenylphosphinic acid and dimethyl methylphosphonate in a mass ratio of 3:1, the initiator is ammonium persulfate, and the auxiliary agent is composed of polyethylene glycol 400 and sodium dodecylsulfonate in a mass ratio of 1:1.

[0048] The preparation method of the modified hydrotalcite comprises the following steps:

[0049] S1. Place 80 nm hydrotalcite in an oven, vacuum dry it at 115 ° C for 5.5 hours to remove physically adsorbed water, cool it to room temperature, add anhydrous ethanol and a modified silane coupling agent, ultrasonicate it at 267 W power for 7 minutes, adjust the pH value to 7.5, heat it to 48 ° C and stir it for 5.7 hours, filter the solid, wash it three times with anhydrous ethanol, and vacuum dry it at 80 ° C for 11.5 hours to obtain a prefabricated hydrotalcite, wherein the mass ratio of the hydrotalcite, anhydrous ethanol and modified silane coupling agent is 22:93:15;

[0050] S2. The prefabricated hydrotalcite and pure ethanol were stirred at 435 rpm for 25 min, furfural was slowly added and stirred at a constant temperature of 63°C for 4.5 h, the liquid was removed by centrifugation, the solid was rinsed four times with pure ethanol, placed in an oven, and vacuum-dried at 90°C to constant weight to obtain a modified hydrotalcite, wherein the mass ratio of the prefabricated hydrotalcite, pure ethanol, and furfural was 19.5:75:2.5.

[0051] Wherein, the preparation of the modified silane coupling agent comprises the following steps:

[0052] L-cysteine ​​was added to a photoinitiator and a 95% volume fraction ethanol solution, and the mixture was ultrasonically treated at a power of 185 W for 13 minutes. Nitrogen gas was introduced to form an inert gas atmosphere, and the mixture was placed under irradiation with ultraviolet light of 365 nm wavelength. A silane monomer was slowly added and magnetic stirring was performed at a speed of 435 rpm for 3.7 hours. The solvent was rotary evaporated and the mixture was vacuum dried at 80° C. to constant weight to prepare a modified silane coupling agent. The mass ratio of the L-cysteine, silane monomer, photoinitiator and ethanol solution was 25.5:31:0.11:215. The photoinitiator was photoinitiator 1173, and the silane monomer was silane coupling agent NQ62.

[0053] A method for preparing a flame retardant adhesive comprises the following steps:

[0054] Preheat the EVA emulsion to 63°C, add methyl acrylate, acrylamide and N-hydroxyacrylamide, modified hydrotalcite, organophosphorus flame retardant and additives and stir, cool, add initiator and continue stirring to obtain a flame retardant adhesive.

[0055] Example 4

[0056] A flame-retardant adhesive for plywood comprises the following components in parts by weight: 70 parts of EVA emulsion, 33 parts of methyl acrylate, 21 parts of acrylamide, 13 parts of N-hydroxyacrylamide, 16 parts of modified hydrotalcite, 5 parts of an organophosphorus flame retardant, 1.0 part of an initiator, and 1.5 parts of an auxiliary agent, wherein the organophosphorus flame retardant is composed of phenylphosphinic acid and dimethyl methylphosphonate in a mass ratio of 3:1, the initiator is ammonium persulfate, and the auxiliary agent is composed of polyethylene glycol 400 and sodium dodecylsulfonate in a mass ratio of 1:1.

[0057] The preparation method of the modified hydrotalcite comprises the following steps:

[0058] S1. Place hydrotalcite with a particle size of 100 nm in an oven, vacuum dry it at 120° C. for 6 h to remove physically adsorbed water, cool it to room temperature, add anhydrous ethanol and a modified silane coupling agent, ultrasonicate it at 300 W power for 8 min, adjust the pH value to 7.5, heat it to 52° C. and stir it for 6 h, filter the solid, wash it three times with anhydrous ethanol, and vacuum dry it at 80° C. for 12 h to obtain a prefabricated hydrotalcite, wherein the mass ratio of the hydrotalcite, anhydrous ethanol and modified silane coupling agent is 23:100:16;

[0059] S2. The prefabricated hydrotalcite and pure ethanol were stirred at a speed of 500 rpm for 30 minutes, furfural was slowly added and stirred at a constant temperature of 65°C for 5 hours, the liquid was removed by centrifugation, the solid was rinsed four times with pure ethanol, placed in an oven, and vacuum-dried at 90°C to constant weight to obtain a modified hydrotalcite, wherein the mass ratio of the prefabricated hydrotalcite, pure ethanol and furfural was 20:80:2.6.

[0060] Wherein, the preparation of the modified silane coupling agent comprises the following steps:

[0061] L-cysteine ​​was added to a photoinitiator and a 95% volume fraction ethanol solution, and the mixture was ultrasonically treated at a power of 200 W for 15 minutes. Nitrogen gas was introduced to form an inert gas atmosphere, and the mixture was placed under irradiation with ultraviolet light of 365 nm wavelength. A silane monomer was slowly added, and the mixture was magnetically stirred at a speed of 500 rpm for 4 hours. The solvent was rotary evaporated and the mixture was vacuum dried at 80° C. to constant weight to prepare a modified silane coupling agent. The mass ratio of L-cysteine, silane monomer, photoinitiator and ethanol solution was 26:32:0.12:220. The photoinitiator was photoinitiator 1173, and the silane monomer was silane coupling agent NQ62.

[0062] A method for preparing a flame retardant adhesive comprises the following steps:

[0063] Preheat the EVA emulsion to 65°C, add methyl acrylate, acrylamide and N-hydroxyacrylamide, modified hydrotalcite, organophosphorus flame retardant and additives and stir, cool, add initiator and continue stirring to obtain a flame retardant adhesive.

[0064] Comparative Example 1

[0065] Compared with Example 4, Comparative Example 1 uses silane coupling agent NQ62 instead of modified silane coupling agent, and the rest are the same.

[0066] Comparative Example 2

[0067] Compared with Example 4, Comparative Example 2 does not use furfural, and the rest are the same.

[0068] Comparative Example 3

[0069] Compared with Example 4, Comparative Example 3 uses benzaldehyde instead of furfural, and the rest are the same.

[0070] Comparative Example 4

[0071] Compared with Example 4, Comparative Example 4 uses acrylamide instead of N-hydroxyacrylamide, and the rest are the same.

[0072] Comparative Example 5

[0073] Compared with Example 4, Comparative Example 5 is different in that the organophosphorus flame retardant is phenylphosphinic acid, and the rest are the same.

[0074] Comparative Example 6

[0075] Compared with Example 4, Comparative Example 6 is different in that the organophosphorus flame retardant is dimethyl methylphosphonate, and the rest are the same.

[0076] The wood is 5-6 years old, with a moisture content of 10%, a size of 300mm×300mm×3mm, and a density of 0.85g / cm 3 The fast-growing poplar wood was used as a veneer, and the adhesives of Examples 1-4 and Comparative Examples 1-6 were used, with the adhesive application amount being 120 g / m 3 After the mixture is laid, it undergoes pre-pressing, penetrating steam pre-pressing, and hot pressing to produce flame-retardant plywood. The hot pressing temperature is 110°C, the time is 180 seconds, and the pressure is 2.5MPa.

[0077] The flame retardant plywood prepared with the corresponding adhesives of Examples 1-4 and Comparative Examples 1-6 were subjected to the following tests, and the test results are shown in Table 1.

[0078] Limiting oxygen index: tested in accordance with GB / T2406.2-2009;

[0079] Bending strength: tested according to GB / T1936.1-2009;

[0080] Table 1 Performance test results

[0081] Limiting oxygen index (%) Flexural strength (MPa) Example 1 38.5 119.8 Example 2 38.8 121.5 Example 3 39.1 123.0 Example 4 38.7 121.3 Comparative Example 1 28.8 105.8 Comparative Example 2 28.0 99.6 Comparative Example 3 35.8 117.8 Comparative Example 4 34.6 112.5 Comparative Example 5 35.2 116.8 Comparative Example 6 34.3 114.2

[0082] From the test results in Table 1, it can be seen that, compared with Comparative Examples 1-6, the adhesives prepared in Examples 1-4 have excellent flame retardant properties, and the plywood prepared therefrom has significant flame retardant effects and mechanical properties.

[0083] Comparative analysis shows that the present invention incorporates hydrotalcite as an inorganic flame retardant. Its layered structure decomposes upon heating to release crystalline water, which exerts a flame retardant effect by absorbing heat, cooling, and diluting combustible gases. After the hydrotalcite is grafted and modified with a silane coupling agent, an organic / inorganic flame retardant material is formed, which improves its dispersibility in the adhesive and avoids a decrease in flame retardant efficiency due to agglomeration. Furthermore, the modified hydrotalcite enhances the interfacial interaction with the adhesive matrix, allowing the flame retardant component to more evenly participate in charring during combustion, thereby reducing the escape of combustible gases.

[0084] The present invention adds cysteine ​​as a raw material containing the S element. The thiol group contained in cysteine ​​can react with the double bond of the silane coupling agent NQ62 to introduce the S element into the system. The S element can dilute the oxygen concentration and capture combustion free radicals by releasing sulfur-containing inert gas during the combustion process, thereby exerting a gas-phase flame retardant effect. After the hydrotalcite surface is grafted with the modified silane coupling agent, multiple amino groups are introduced, which can react with the aldehyde group of furfural to form a Schiff base structure. The Schiff base structure is easily decomposed at high temperature to produce non-flammable gases such as nitrogen, while promoting the system to The condensed phase forms a dense carbon layer, which blocks the transfer of heat and combustibles. In addition, furfural contains a furan structure, and its conjugated structure can improve the stability and density of the carbon layer, delaying heat conduction and combustible release in the condensed phase. The presence of the furan ring works synergistically with the Schiff base structure and S-containing components through the dual mechanisms of gas phase flame retardancy and condensed phase flame retardancy. Specifically, the S element and the furan structure enhance the antioxidant and barrier properties of the carbon layer, and the Schiff base structure and the number of amino groups regulate the carbonization efficiency, which together significantly improve the flame retardant properties of the adhesive material.

[0085] The present invention adds N-hydroxyacrylamide as a polymerization monomer, so that the polymer contains multiple hydroxyl groups, which can form hydrogen bonds with the carboxyl groups on the modified hydrotalcite, effectively promoting the dispersibility of the modified hydrotalcite in the system.

[0086] The phenylphosphinic acid in the adhesive of the present invention contains a phenyl structure that imparts a certain rigidity and heat resistance to the carbon layer. The phosphorus-containing compound produced by the decomposition of dimethyl methylphosphonate can enhance the oxidation resistance and thermal stability of the carbon layer, making the carbon layer less likely to crack or decompose at high temperatures and continuously exerting a flame retardant effect. In addition, the good solubility of dimethyl methylphosphonate helps to disperse the phenylphosphinic acid in the material, thereby more fully exerting the flame retardant effect.

[0087] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any person skilled in the art can make some changes or modifications to equivalent embodiments using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any indirect modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A flame retardant adhesive for plywood, characterized in that: The composition comprises the following components in parts by weight: 52-70 parts of EVA emulsion, 28-33 parts of methyl acrylate, 15-21 parts of acrylamide, 10-13 parts of N-hydroxyacrylamide, 12-16 parts of modified hydrotalcite, 3-5 parts of organophosphorus flame retardant, 0.8-1.0 parts of initiator and 0.8-1.5 parts of auxiliary agent; The preparation method of the modified hydrotalcite comprises the following steps: S1. Dry the hydrotalcite in an oven at high temperature, cool it, add anhydrous ethanol and a modified silane coupling agent, mix them ultrasonically, adjust the pH value, heat and stir, filter and take the solid, wash it, and vacuum dry it to obtain a prefabricated hydrotalcite; S2. Stir and disperse the prefabricated hydrotalcite and pure ethanol, slowly add furfural and stir at a constant temperature, remove the liquid by centrifugation, rinse the solid, and dry it in a vacuum oven to obtain the modified hydrotalcite; The preparation of the modified silane coupling agent comprises the following steps: L-cysteine ​​is added to a photoinitiator and a solvent and ultrasonically dispersed, an inert gas is introduced to form an inert gas atmosphere, and the mixture is placed under ultraviolet light. Silane monomer is slowly added with magnetic stirring, the solvent is removed by rotary evaporation, and vacuum drying is performed to obtain a modified silane coupling agent.

2. The flame retardant adhesive for plywood according to claim 1, characterized in that: The organic phosphorus flame retardant is one or more of phenylphosphinic acid, dimethyl methylphosphonate, diethyl ethylphosphonate, and diphenyl phenylphosphonate.

3. The flame retardant adhesive for plywood according to claim 1, characterized in that: The initiator is a water-soluble peroxide initiator, and the water-soluble peroxide initiator is one or both of ammonium persulfate and potassium persulfate.

4. The flame retardant adhesive for plywood according to claim 1, characterized in that: The auxiliary agent consists of polyethylene glycol 400 and sodium lauryl sulfate.

5. The flame retardant adhesive for plywood according to claim 1, characterized in that: In step S1, the high-temperature drying is vacuum drying at 100-120°C for 4-6 hours, and the particle size of the hydrotalcite is 50-100 nm.

6. The flame retardant adhesive for plywood according to claim 1, characterized in that: In step S1, the ultrasonic mixing is performed at a power of 200-300 W for 5-8 minutes, the heating stirring is performed at 40-52° C. for 5-6 hours, and the mass ratio of the hydrotalcite, anhydrous ethanol and modified silane coupling agent is 20-23:80-100:12-16.

7. The flame retardant adhesive for plywood according to claim 1, characterized in that: In step S2, the stirring and dispersing is stirring at a rotation speed of 300-500 rpm for 15-30 minutes, the constant temperature stirring is stirring at a constant temperature of 58-65°C for 4-5 hours, and the mass ratio of the prefabricated hydrotalcite, pure ethanol and furfural is 18-20:60-80:2.2-2.

6.

8. The flame retardant adhesive for plywood according to claim 1, characterized in that: In the preparation of the modified silane coupling agent, the ultraviolet lamp irradiation is ultraviolet irradiation at a wavelength of 365nm, the magnetic stirring is stirring at a speed of 300-500rpm for 3-4h, the photoinitiator is photoinitiator 1173, and the silane monomer is silane coupling agent NQ62.

9. The flame retardant adhesive for plywood according to claim 1, characterized in that: In the preparation of the modified silane coupling agent, the mass ratio of L-cysteine, silane monomer, photoinitiator and solvent is 24-26:28-32:0.10-0.12:200-220.

10. A method for preparing the flame retardant adhesive for plywood according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: Preheat the EVA emulsion to 60-65°C, add methyl acrylate, acrylamide and N-hydroxyacrylamide, modified hydrotalcite, organophosphorus flame retardant and additives, stir, cool, add initiator and continue stirring to obtain the product.